Often Overlooked: Understanding and Meeting the Current Challenges of Marine Invertebrate Conservation - Chen, Emily Yi-Shyuan (Frontiers in Marine Science, 2021)
Making up over 92% of life in our oceans, marine invertebrates inhabit every zone in the water column, with contributions ranging from ecosystem functioning to socioeconomic development. Compared to charismatic species, marine invertebrates are often underrepresented in IUCN reports and national conservation efforts. Because of this, as climate change intensifies in conjunction with increasing anthropogenic pressures such as habitat destruction, many marine invertebrates are at risk of silently heading toward extinction. However, public perception has shifted in recent years due to the growing awareness of the important roles these invertebrates play in marine and human life. This change may promote greater support for future research and conservation campaigns of key species. This review highlights the importance of marine invertebrates, the environmental and anthropogenic stressors they are currently facing, and the inherent challenges in their successful conservation. Potential solutions to fill the gaps in current knowledge will be also explored in the context of recent globalization and technological advancements. The loss of marine invertebrate biodiversity will have cascading ecological, economic, and sociological repercussions, so compiling key information into a holistic review will add to the conversation of the importance of global marine invertebrate conservation.